Hongos patógenos de insectos en Argentina (Zygomycetes: Entomophthorales) - López Lastra, C. C.; Scorsetti, A. C. (Revista de Biología Tropical, 2006)
Three species of Entomophthorales entomopathogenic fungi (Zygomycotina: Zygomycetes) have been identified from insects in agricultural crops (Buenos Aires Province, Argentina): Zoophthora radicans Batko (Brefeld); Entomophthora planchoniana Cornu and Pandora gammae (Weiser) Humber. Fungal structure measurements are reported.